2009
DOI: 10.1063/1.3276770
|View full text |Cite
|
Sign up to set email alerts
|

Millisecond flash lamp annealing of shallow implanted layers in Ge

Abstract: Shallow n+ layers in Ge are formed by phosphorus implantation and subsequent millisecond flash lamp annealing. Present investigations are focused on the dependence of P redistribution, diffusion and electrical activation on heat input into the sample and flash duration. In contrast to conventional annealing procedures an activation up to 6.5× 1019 cm-3 is achieved without any dopant redistribution and noticeable diffusion. Present results suggest that independently of pretreatment the maximum activation should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…These junctions are integrated with SPA GeO 2 High-k gate stack to obtain a high performance Ge nMOSFET with significantly reduced contact resistance. Ion Implantation RTA Sb-8 x 10 18 / As 8x10 18 / P-2x10 19 /B-1x10 20 [6] Ion Implantation Flash Anneal P -6x10 19 [7] In-situ doping Thermal P-1x10 19 [8] Gas Phase Doping RTA As-1x10 19 [9] Ion Implantation Furnace Anneal P -8 x 10 18 [10] Ion Implantation Laser Thermal Processing (LTP) …”
Section: Discussionmentioning
confidence: 99%
“…These junctions are integrated with SPA GeO 2 High-k gate stack to obtain a high performance Ge nMOSFET with significantly reduced contact resistance. Ion Implantation RTA Sb-8 x 10 18 / As 8x10 18 / P-2x10 19 /B-1x10 20 [6] Ion Implantation Flash Anneal P -6x10 19 [7] In-situ doping Thermal P-1x10 19 [8] Gas Phase Doping RTA As-1x10 19 [9] Ion Implantation Furnace Anneal P -8 x 10 18 [10] Ion Implantation Laser Thermal Processing (LTP) …”
Section: Discussionmentioning
confidence: 99%
“…In Si applications high-temperature millisecond anneals (laser and flash) are popular and are beginning to be applied to Ge (37)(38)(39)(40). As the melting point of Ge is 937 °C, a low-temperature process such as solidphase-epitaxial-regrowth appears to be another solution (41).…”
Section: Metastable Solubility and Damage Annihilationmentioning
confidence: 99%
“…Thereby enhanced diffusion due to implantation damage is also suppressed. For example, W€ undisch et al 64,88 have demonstrated by millisecond flash lamp annealing of shallow P implants that an electric active P concentration of about 6.5 Â 10 19 cm À3 can be realized without noticeable P diffusion. Similarly, high concentrations of electrically active As and Sb were obtained by laser annealing of As-and Sb-implanted Ge.…”
Section: B Experimental Evidence For Donor Deactivationmentioning
confidence: 99%